Longitudinal association between maternal psychological stress during pregnancy and infant neurodevelopment: The moderating effects of responsive caregiving - Shi, Yuyang; Zhang, Yudi; Wei, Qian; Ma, Xuemei; Zhang, Yunhui; Shi, Huijing (Frontiers in Pediatrics, 2022)
Background: Little is known regarding the role of responsive caregiving in the association between maternal psychological stress and child neurodevelopment. We therefore herein investigated the relationship between maternal psychological stress during pregnancy and children’s neurodevelopment with modifications in responsive caregiving. Methods: A total of 3603 mother-child pairs were recruited from the Shanghai Maternal-Child Pairs Cohort, and we assessed maternal psychological stress using the Life Events Scale for Pregnant Women (LESPW) during early and late pregnancy. Early neurodevelopment of infants at six and 12 months of age was also evaluated using the Age and Stage Questionnaire, Third Edition (ASQ-3). The two-month-old infant nursing-care questionnaire was designed based on the Five Elements of Parenting Care Framework released by the World Health Organization (WHO), and used to evaluate the levels of early responsive caregiving for infants. Multivariate logistic regression analysis was then applied to determine the association between maternal psychological stress during pregnancy and child development. Results: The suspected developmental delay rate of infants aged six and 12 months ranged between 13.3% and 24.5%. After adjusting for confounders, we noted that high maternal subjective events stress during early pregnancy was associated with an increased risk of suspected developmental delay in problem-solving domains at 12 months of age (aOR = 1.51; 95% CI, 1.09–2.20). High general negative objective events stress during late pregnancy also constituted a risk factor for development in the personal-social domain at 12 months of age (aOR = 1.57; 95% CI, 1.13–2.19). Remarkably, we noted in infants with insufficient responsive caregiving that there were greater associations between the risk of general maternal negative objective events during late pregnancy and personal-social domain at 12 months of age (aOR = 2.06; 95% CI, 1.15–3.68). Similarly, there was a greater association between the risk for maternal subjective events during early pregnancy and problem solving at 12 months of age (aOR = 1.55; 95% CI, 1.11–2.34). Conclusions: Maternal psychological stress during pregnancy was predominantly associated with suspected developmental delay in infants at six and 12 months of age, and these associations were modified by early responsive caregiving.